Integração da avaliação da percepção de medidas de minimização para o ruído de tráfego rodoviário, em estudos de impacte ambiental - Antunes, S. (2011)
This paper presents a summary of psychoacoustics tests made in order to assess the perception of noise mitigation measures. Question were addressed in order to understand the sound perception, the visual assessment of noise barriers from photographs, and the degree of pleasantness and corresponding effectiveness of picture and sound from behind noise barriers. Comparison between sounds of a vehicle passage in different pavements and the association between the physical and perceptual data are also presented. The results suggest the importance of public information about the noise mitigation measures and the integration of public perceptions in noise impact studies. Advantage of computer technology can be taken for the presenting information to the public (including sound recordings) in order to assess to the perception and information about the visual noise barriers.